Investigations on the Changes of Serum Proteins in Rabbits after Trimeresurus stejnegeri Venom Injection via Mass Spectrometry-Based Proteomics. (24th June 2022) - Wang, Shijun; Yang, Weilian; Shi, Wanling; Chen, Fuwei; Shen, Fanghua; Zhang, Meiji; Su, Qiuxiang; Shi, Chao; Yu, Qinyao; Chen, Tao
Abstract : Purpose . There are few studies on protein phosphorylation in the process of snake poisoning. The purpose of this study was to investigate the toxic mechanism of Trimeresurus stejnegeri at the protein level by determining the differential expression of phosphorylated proteins in rabbits after poisoning using proteomics. Methods . The Trimeresurus stejnegeri venom model in rabbits was established by intramuscular injection of 20 mg/kg venom. The serum was collected and the differential expression of phosphorylated proteins in the serum was determined by the iTRAQ technology, TiO2 enriched phosphorylated peptides, and the mass spectrometry analysis. The functional analysis was conducted using ClueGO software and the related mechanism was evaluated by the network analysis of biological interaction. The expression level of related proteins was determined by the Western blotting assay. Results . Compared to the control group, 77 differentially expressed proteins were observed in the model group. These proteins were closely associated with the complement and agglomerate cascade signaling pathways, the HIF signaling pathway, the pentose phosphate pathway, and the cholesterol metabolism signaling pathway. According to the results of network analysis, TF and SCL16A1 were determined as the core proteins, which were identified by the Western blotting assay. Conclusion . The present study provided valuable phosphorylation signal transduction resources for investigating the toxic mechanism and the therapies for Trimeresurus stejnegeri poisoning.